Новая цикадка рода Xestocephalus van Duzee (Homoptera, Cicadellidae) из Закавказья - Логвиненко, В.Н. (Вестник зоологии, 1981)
A description is given for Xestocephalus cristifer sp. n. from the Azerbaijan SSR (Talysh, Birmai) and the Georgian SSR (Gardebani). 'The new species is most closely related to X. guttatus Motsch. from which it differs in the acuminate part of the penis stem, in the presence of a membranous pecten on the dorsal side, in straight stem and a gonopore more remote from the apex.